The Religious Architecture in Algeria during the Ottoman Period (An Analytical Study of Archaeological and Historical Evidence) - El khir, Metrouh Oum (Journal of Ecohumanism, 2025)
The mosques of the Ottoman period in the city of Algiers represent an important stage in the development of religious architecture in general and mosque architecture in particular, during a period that extended from the early sixteenth century to the beginning of the nineteenth century. From the moment of their establishment in Algiers, the Ottomans showed great interest in constructing mosques—an interest closely linked to the prevailing political and administrative system of the time. During this period, the city witnessed remarkable urban expansion; its boundaries extended, its infrastructure developed, and it was surrounded by fortified walls that enclosed a variety of architectural structures, among which mosques were the most prominent and visually dominant in the urban landscape. Within this context, this research sheds light on two outstanding architectural models from the Casbah of Algiers: the Mosque of the Dey’s Palace and the Ketchaoua Mosque, as two historical landmarks that remain standing to this day. The study addresses them through a detailed historical, architectural, and artistic analysis, accompanied by a technical and artistic record for each mosque. This record highlights their archaeological and architectural features and clarifies the points of convergence and divergence between inherited local elements and those of Ottoman origin, with the aim of providing a deeper understanding of the religious architectural identity in Algeria during the Ottoman era.